The impact of nonosteogenic factors on the expression of osteoprotegerin and RANKL during human fracture healing. Issue 7 (July 2019) - Starlinger, Julia; Kaiser, Georg; Thomas, Anita; Sarahrudi, Kambiz
Abstract : Objectives: The osteoprotegerin (OPG) and receptor activator of nuclear factor kappa-B ligand (RANKL) balance is of the utmost importance in fracture healing. The aim of this study was therefore to investigate the impact of nonosteogenic factors on OPG and RANKL levels. Methods: Serum obtained from 51 patients with long bone fractures was collected over 48 weeks. The OPG and serum sRANKL (soluble RANKL) concentrations were measured using enzyme-linked immunosorbent assay (ELISA). Smoking habit, diabetes, and alcohol consumption were recorded. Results: Age and sex greatly influenced preoperative serum levels of OPG and sRANKL but differences were even more pronounced during fracture healing. Statistical significance was observed for overall serum levels of OPG (p = 0.001) and sRANKL (p < 0.001) in older men and women (age greater than 50 years). Interestingly, OPG levels increased over time in older women but decreased over time in older men. Conclusion: These data suggest that nonosteogenic factors, most significantly age and sex, have a major impact on sRANKL and OPG levels. Given the established association of OPG and sRANKL levels and nonunion, these findings seem to be of clinical relevance. Cite this article : J. Starlinger, G. Kaiser, A. Thomas, K. Sarahrudi. The impact of nonosteogenic factors on the expression of osteoprotegerin and RANKL during human fracture healing. Bone Joint Res 2019;8:349–356. DOI: 10.1302/2046-3758.87.BJR-2018-0116.R3.